Outcomes of Surgical Management of Varicose Veins with and Without Venous Stripping: A Comparative Study - Dr. Katti Ravi Kumar; Dr Kari Veerabhadra Swamy; Dr. Mude Sarala; Dr Megavath Motilal (International Journal of Pharma and Bio Sciences, 2023)
Varicose veins are tortuous, widened veins in the subcutaneous tissues of the legs and are often visible. Invasive management methods include sclerotherapy, Trendelenburg operation, GSV stripping, perforator ligation, sub-fascial endoscopic perforator surgery (SEPS), and stab avulsion. The present study aimed to compare outcomes of surgical management of varicose veins with and without venous stripping at Siddhartha Medical College, Vijayawada, Andhra Pradesh, India. The study’s objectives include comparing early ambulation of the patient, healing of wounds, postoperative hospital stay, postoperative pain relief, and recurrence between the two groups. It is an interventional, randomized, single-blinded study. 100 patients admitted with varicose veins at the tertiary care center Siddhartha Medical College, Vijayawada, Andhra Pradesh, from March 2021 to September 2022, were taken as the study sample. 100 patients were randomized in groups I and II, each containing 50. Group I included patients who underwent saphenofemoral flush ligation(SFL) by stripping the great saphenous vein up to the knee. Group II included patients who underwent SFL and subfascial ligation of the incompetent perforators in the thigh and leg. Patients were followed up for six months. Results showed no significant difference in the mean age of patients in both groups. 72% of patients were males. Early ambulation was significantly good among patients without venous stripping (Group II). The two groups have no significant difference in wound healing and duration of postoperative hospital stay, pain relief, and recurrence rate. 8% of patients had recurrence during the follow-up period in group I. Sapheno femoral junction (SFJ) flush ligation with incompetent perforators ligation without venous stripping is better than SFJ flush ligation with incompetent perforators ligation with venous stripping.